STRATEGI PENERIMAAN RETRIBUSI PARKIR TEPI JALAN UMUM PADA MASA PANDEMI COVID-19 DI KOTA DENPASAR - Yuniari, Ni Komang Yuli; Yudartha, I Putu Dharmanu; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
This study aims to determine the strategy implemented by the Regional Public Company Bhukti Praja Sewakadarma during the COVID-19 pandemic in Denpasar City. In this study the author uses a type of qualitative research with descriptive methods. The theory used in this research is the theory of strategic management process by Hunger and Whelen which consists of four indicators, namely environmental scanning, strategy formulation, strategy implementation, and evaluation and control. The findings in this study indicate that the four indicators have been carried out by the Regional Public Company Bhukti Praja Sewakadarma, but have not been optimal. Keywords: Strategy, Parking Retribution, Public Company Bhukti Praja Sewakadarma